Academic industry to create joint forum. - Fraser, Fiona (Bookseller, 2004)
Academic publishers and booksellers plan to set up a joint academic forum similar to the one established by the general trade. At the 33rd annual conference of the BA's Academic, Professional and Specialist Booksellers Group, chairman Gareth Hardy and his counterpart on the PA's Council of Academic and Professional Publishers, Rod Bristow, agreed that the establishment of a cross-industry forum would help both groups to move forward in areas of mutual interest. These included the challenges presented by the migration from print to electronic products, the control of intellectual property copyright, and the better servicing of the end customers.